1 - Land in the Political Economy of African Development: Alternative Strategies for Reform - Moyo, Sam (Africa Development, 2007)
Since 2000, there has been an escalation of land-related conflicts in Zimbabwe, Côte d’Ivoire, the Delta region of Nigeria and elsewhere in Africa. These con- flicts are examples of numerous national struggles for access to land in Africa and reflect the failure of the African state to address the land and development nexus on the continent. The land question in Africa is a by-product of globalised control of land, natural resources and minerals in general, reflecting incomplete decolonisation processes in ex-settler colonies along with the penchant for for- eign ‘investment’ in a neo-liberal policy framework that marginalises the rural and urban poor. Global finance capital is increasingly entangled in conflicts over land, as the exploitation of oil, minerals and natural resources expands into new African enclaves that highlight the external dimension of distorted devel- opment. These processes define the significance of land in the political economy of African development. This paper examines the complex social and political contradictions that shape land struggles, including their colonial and post-inde- pendence trajectory. The failures of neo-liberal land reforms, based on market forces and their confrontation by popular demands for redistributive reforms are discussed.